LIQUID SOAP WITH ADDITIONS SARGASSUM (Sargassum polycystum) EXTRACT - Allya Zahra; Irfan Restu Fauzan; Intan Oktavia D; Setyaningrum Setyaningrum; Sujuliyani Sujuliyani (Buletin Jalanidhitah Sarva Jivitam, 2019)
Research on making Sargassum soap with the addition of Sargassum polycystum seaweed was carried out for 2 months at the Jakarta College of Fisheries. This study aims to determine the flow of the Sargassum polycystum soap making process, find out how to make Sargassum polycystum soap extracts, determine the quality of liquid soap produced through sensory, chemical and biological tests. This research uses direct research methods. Research results show that the process of making liquid soap extracts include: preparation of raw materials, maceration, evaporation, rinsing and drying. The process of making liquid soap, among others, by adding chemicals include: texafon S, sodium sulfate, aquades, texafon EVR, glycerin, olive oil Sargassum extract, perfume. Based on the results of sensory testing of soap by adding the concentration of Sargassum extract with soap that did not get the addition of Sargassum, it has an average rating that is almost the same. In addition to knowing the quality of Sargassum, chemical, microbiological and anti-bacterial tests were also carried out. Chemical tests include: Moisture content, specific gravity, viscosity, foam stability, Ph test, and free alkali. While the microbiological tests conducted on soap are: ALT.Keywords: Liquid soap, Seaweed, Sargassum, Extract